Initial teacher education for inclusion, equity, and equality: An analysis of practicum reports - Maria Alfredo Moreira; Manuel António Silva; Ana Sofia Afonso (Revista Brasileira de Educação do Campo)
The text analyses the extent to which teacher practicum reports in Portugal attend to issues of inclusion, equity, and equality that ensure the fulfillment of the right to education. We look at the titles, keywords, and abstracts in order to select the practicum reports presented for preschool and primary education teacher preparation in all public higher education institutions in Portugal between 2020 and 2023. Then we read the whole texts. Through quantitative and qualitative content analysis of student teachers’ reports, within an interpretive framework, we evidence the extent to which their practicum experience promotes inclusive, egalitarian and equitable educational practice, as evidenced in the texts. We conclude that only 11,5% of the analysed reports take these issues as drivers for pedagogical practice. Those that do explore gender issues, intercultural education, special needs education, and inclusiveness in general the classroom, in a way that can be transformative for children’s lives. However, the persistence of the invariants of educational action, like textbooks, teacher isolation, the compartmentalization of the subjects, the emphasis on academic literacy development, or summative assessment, acts as structural obstacles to sustainable impact and to inclusive, equal, and equitable educational practice.